Strengthening Entrepreneurial Creativity Through Industry-Based Learning: A Community Engagement Program at Modena Home Center - Zahara Fatimah; Arina Luthfini Lubis; Supardi; Kamelia Santika (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
Entrepreneurship education in vocational higher education requires learning approaches that bridge classroom theory and real-world business practices. However, students often have limited opportunities to directly observe how entrepreneurial concepts are implemented in professional industrial settings. Therefore, a community engagement program entitled “Strengthening Entrepreneurial Creativity Through Industry-Based Learning: A Community Engagement Program at MODENA Home Center” was conducted to enhance students’ entrepreneurial understanding and creativity through direct industry exposure. The program involved vocational students from Batam Tourism Polytechnic and was implemented in collaboration with MODENA Home Center Batam, a leading household appliance company. The activities consisted of participant orientation, company profile presentation, showroom observation, product knowledge sessions, interactive discussions, and reflective evaluation. To assess the effectiveness of the program, pre-test and post-test evaluations were administered before and after the activity. The results indicated a significant improvement in students’ understanding of entrepreneurship concepts and modern kitchen equipment, as reflected in the increased post-test scores compared to the pre-test scores. Students also demonstrated greater awareness of customer service, product positioning, marketing strategies, and business operations within a professional retail environment. Furthermore, the program strengthened collaboration between academia and industry while providing MODENA Home Center with opportunities to increase brand exposure among Generation Z consumers. The findings suggest that industry-based learning is an effective approach for strengthening entrepreneurial creativity and providing meaningful experiential learning opportunities for vocational students. Therefore, similar collaborative programs should be continuously developed to support entrepreneurship education and industry-academia partnerships.